An outcome evaluation of the Centre of Science and Technology - Lemmon, Danielle Kelly (Institute for Monitoring and Evaluation, 2017)
Globally education policy, practice and research has emphasized the importance of science, technology, engineering and mathematics (STEM) secondary schools in diminishing the skills-gap in STEM disciplines. This research presents an outcome evaluation of a STEM-focused secondary school in the Western Cape of South Africa. The evaluation focused on the academic performance of the COSAT learners in comparison to learners who did not form part of the programme. Additionally, the evaluation focused on the retention of COSAT alumni in STEM disciplines. With increased academic performance of COSAT learners as well as the long-term retention of learners in the STEM field this research provides evidence of the intermediate and long-term impact of a STEM secondary school.